Assessing the use and understanding of the Portuguese Heat–Health Warning System (ÍCARO). (13th November 2019) - Leite, A; Santos, A J; Silva, S; Nunes, B; Mexia, R; Rodrigues, A P
Abstract: Background: Heatwaves can lead to increased mortality. Portugal has a Heat-Health Warning System (HHWS) in place (ÍCARO system). Researchers at the Instituto Ricardo Jorge send a daily report with heat-related mortality forecasts to key stakeholders (e.g. Heat-Health Action Plans (HHAP) staff). HHAP practitioners issue warnings and implement measures to prevent heatwaves-related mortality. ICARO is amongst the recommended data sources to assess risk and issue warnings but its use and understanding is unknown. Therefore, we aimed to assess ÍCARO's use and understanding by key HHAP practitioners. Methods: We conducted semi-structured interviews with national and regional HHAP practitioners. Interviews were recorded, transcribed, and analysed using thematic content analysis. Intercoder reliability was applied to a sample of segments from 5 of 6 interviews. Results: We conducted 6 interviews with 9 professionals (mean time 52 minutes). We identified 4 categories: Report's content and presentation, Report's reception and communication, ÍCARO and risk assessment, Other issues. Practitioners use ÍCARO and perceived it as very relevant tool. However, they mentioned several questions on its interpretation. Practitioners also felt their questions were not fully answered, given researchers' use of statistical terms. Finally, practitioners referred the need to assess risk at the local level, information not currently provided. We also identified the need for improved communication and report's clarity. Conclusions: Our study stresses the need for an integrated collaboration between experts within HHWS and HHAP. Despite ICARO's understanding being challenging, practitioners consider it a relevant tool. Researchers should use less statistical language and clarify ÍCARO interpretation. Practitioners' needs should be considered when developing or revising tools. We are currently implementing some of these recommendations in an attempt to close the gap between researchers and practitioners. Key messages: Portuguese Heat–Health Action Plans practitioners use heat-related mortality forecasts (ICARO) and perceived it as very relevant instrument. However there find ICARO's interpretation challenging. Portuguese Heat/Health Action Plans Practitioners' needs should be considered when revising or developing tools, and notes should be added to clarify statistical/technical concepts.